The role of attachment to parents, peers and teachers in predicting academic self-handicapping of first secondary school students - Khan Mohammadi, Reihaneh; Delavarpour, Mohamadagha; Rezaei, Ali Mohammad; Najafi, Mahmoud (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Academic self-disability is one of the less known strategies used to explain failure. The aim of the present study was to investigate the role of attachment to parents, peers and teachers in predicting academic self-handicapping of first secondary students. Methods: This research was descriptive and correlational. The statistical population of the present study included all students (girls) of the first secondary level in Tehran in the academic year 2019-2020, which number was approximately 1840000, and 384 people were selected to determine the sample size using available sampling. The research tools included the academic self-handicapping scale, the revised list of attachment to parents and peers, and the scale of attachment to the teacher. In order to analyze the data, Pearson's correlation test and multiple linear regression were used. Results: The results have shown that there is a negative and significant relationship between attachment to parents, peers and teachers (acceptance and non-rejection) and self-disability (P